2020
DOI: 10.1161/circresaha.119.315821
|View full text |Cite
|
Sign up to set email alerts
|

Exome-Based Case-Control Analysis Highlights the Pathogenic Role of Ciliary Genes in Transposition of the Great Arteries

Abstract: Rationale: Transposition of the great arteries (TGA) is one of the most severe types of congenital heart diseases. Understanding the clinical characteristics and pathogenesis of TGA is, therefore, urgently needed for patient management of this severe disease. However, the clinical characteristics and genetic cause underlying TGA remain largely unexplored. Objective: We sought to systematically examine the clinical characteristics and genetic cause for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…In our study, all the predicted deleterious NSUN5 mutations in TOF patients were heterozygous. A recent study reported that a 33% transposition of the great arteries, a type of OFT defect, had more than one candidate gene hit by putative heterozygous deleterious variants and that the cases might have been affected by polygenic inheritance (Liu et al, 2020). Such an inheritance pattern might account for the findings of our genetic analyses of TOF patients.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, all the predicted deleterious NSUN5 mutations in TOF patients were heterozygous. A recent study reported that a 33% transposition of the great arteries, a type of OFT defect, had more than one candidate gene hit by putative heterozygous deleterious variants and that the cases might have been affected by polygenic inheritance (Liu et al, 2020). Such an inheritance pattern might account for the findings of our genetic analyses of TOF patients.…”
Section: Discussionmentioning
confidence: 68%
“…Studies have used gnomAD as either the primary or secondary external control sample. While many of these studies are in European [39][40][41] or East Asian 42,43 ancestral groups, which we find to contain little to no other continental reference ancestry, some studies use gnomAD groups that contain admixture (e.g., African/African American, American/Latinx, and South Asian) for comparison without adjusting population structure. 6,16,44 We evaluate the potential utility of Summix's ancestryadjusted AF by producing ancestry-adjusted AFs for Clin-Var variants, for the CF variant p.Phe508del in CFTR, and for a case-control analysis of PADI3, a gene where gno-mAD was used as an external control sample to identify as-sociation with central centrifugal cicatricial alopecia in women with African ancestry.…”
Section: Discussionmentioning
confidence: 96%
“…Though this evidence seems to suggest a possible link between RYR1 variants and conotruncal heart defects, further evidence supporting the link runs short. In a large study of 66 family trios with a phenotype of d‐TGA, none were found to have RYR1 variants on whole‐exome sequencing (Liu et al, 2020 ). This study had limited sensitivity for intronic variants though, a possible limitation.…”
Section: Discussionmentioning
confidence: 99%